2018
DOI: 10.1111/jre.12529
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of glycyrrhetinic acid in the gingival sulcus inhibits attachment loss in lipopolysaccharide‐induced experimental periodontitis in rats

Abstract: In the present study, we showed that GA inhibits periodontal destruction in the rat experimental periodontitis model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Consequently, some of the LPS may leak from the injection site. As a result, the application of LPS at a higher concentration might be implemented to compensate for the loss (19).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, some of the LPS may leak from the injection site. As a result, the application of LPS at a higher concentration might be implemented to compensate for the loss (19).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, by preventing the activation of NF-κβ, glycyrrhetinic acid can reduce the expression of IL-8, which increases vascular endothelial permeability in HMEC ( 117 ). Some researchers applied glycyrrhetinic acid locally to the gingival sulcus of the rat periodontitis model and found that glycyrrhetinic acid could effectively inhibit the formation of LPS-stimulated immune complex and inflammatory cell infiltration, and no loss of attachment was observed ( 159 ).…”
Section: Medicine Food Homology Plants Inhibit Host Inflammatory Resp...mentioning
confidence: 99%
“…In vivo test using a rat periodontitis model treated with glycyrrhizin revealed the downregulation of HMGB1, IL-6, and IL-1β in the gingival crevicular fluid and periodontal tissue (115). AGEs receptors (RAGE) in tissues and plasma of diabetic patients bound to HMGB1 are key in the association between periodontitis and diabetes (158). In diabetic mice with periodontitis, glycyrrhizic acid can suppress the production of HMGB1 and RAGE mRNA in the gingiva and serum and lessen the inflammatory response of the periodontal tissue (116).…”
Section: Saponinmentioning
confidence: 99%
“…The main active constituent of licorice is Glycyrrhetinic acid (GA), which is obtained from the extract of licorice root. GA shows anti-inflammatory effects due to the similarity in its chemical structure with glucocorticoids by initiation of glucocorticoid receptor signaling and also by inhibiting the classical complement pathway [12]. Licorice flavonoid components include chalcones, flavones, and isoflavones, which show antimicrobial [13], antiviral [14], antiinflammatory [15], antidiabetic, antitumor, immunoregulatory [16], hepatoprotective [17] and neuroprotective activities [18].…”
Section: Introductionmentioning
confidence: 99%